Pengaruh Kebersihan Lingkungan Terhadap Kesehatan Masyarakat Tigaras Dusun Labuhan - Novia Elisabet Malau; Martina Estepania Hinal Siahaan; Rina Wati Lumban Gaol; Angela Mericci Alpa Manurung; Nimerodin Tafonao; Rebecca Adelia Situmorang; Devi Inriani Br. Purba; Opris Sianipar; Wilda Anicheta Sinaga (Lembaga Pengembangan Kinerja Dosen, 2024)
This service to the community through the Real Work Lecture (KKN), is one form of supportive activity that strengthens the relationship between the community and students. With this activity, students can also get closer or more easily socialize with the local community. Then in implementing a healthy lifestyle, namely by paying attention to the garbage around so as not to interfere with the waterways so that they are not clogged. And it is also very important to dispose of garbage in its place, in addition to reducing waste, it also reduces diseases that can attack the community.